A seroprevalence study of camel brucellosis in three camel-rearing regions of Ethiopia - Teshome, H.; Molla, B.; Tibbo, Markos (Springer, 2003)
A cross-sectional investigation was made into the seroprevalence of brucellosis in camels in three arid and semi-arid camel-rearing regions of Ethiopia (Afar, Somali and Borena) between November 2000 and April 2001. When sera collected from 1442 accessible camels were screened with the Rose Bengal plate test (RBPT), 82 (5.7%) of them reacted. The results of a complement fixation test (CFT) on those sera that had given a positive reaction to the screening test then indicated a 4.2% prevalence of brucellosis in the tested camels. There was a significant difference in the prevalence of brucellosis ( 2 = 7.91, p<0.05), which was highest in Afar (5.2%) followed by Somali (2.8%) and Borena (1.2%) regions. Camels in Afar had a four times higher risk of brucellosis with an odds ratio (OR) of 4.34 (confidence interval, CI = 1.76–10.72, p<0.001) compared to the risk in Borena. Likewise, Afar had higher risk (OR = 1.76, 1.13–2.74, p<0.05) than that in Somali. There was no significant difference in seroprevalence between the sexes (p>0.05). Although a higher prevalence (6.3%) was observed in camels over 3 years old in Afar, there was no significant overall age difference (p>0.05).